Modern Scientific Research On Noise Reduction In Production Processes - Sh.G. Musayev (Genius Journals, 2025)
This article examines modern scientific research on the problem of noise and its reduction in industrial production processes, in particular, in machine-building workshops and related enterprises. Noise is one of the dangerous production factors in the occupational health and safety system, and its high level leads to a decrease in hearing, diseases of the nervous system, and a decrease in labor productivity in workers. Although world and national standards indicate that noise above 85 dBA contradicts regulatory requirements, in workshops using heavy mechanical equipment, indicators up to 95-100 dBA are observed. The article analyzes scientific research conducted in recent years and separately considers three main noise reduction strategies - direct impact on the noise source, the use of acoustic barriers in the path of propagation, and the use of personal protective equipment. The effectiveness of acoustic screens and absorbing panels, new types of noise-absorbing materials, vibrationreducing structural solutions, and protective equipment that meet ergonomic requirements were analyzed. It is also shown that special clothing and innovative solutions based on acoustic filtration have the possibility of application in the production environment. The results of the analysis show that in the fight against noise, it is not enough to take only one approach, but it is necessary to apply a set of measures. At the same time, the issues of integration with technological processes, economic efficiency, and material stability in high-temperature zones have not yet been fully resolved. In future scientific research, noise control in real time using intelligent control systems, the use of composite materials, and the development of environmentally safe solutions are proposed as promising areas.
Keywords: Industrial noise; noise protection equipment; research work